Computational Study on the Different Ligands Induced Conformation Change of β2 Adrenergic Receptor-Gs Protein Complex - Bai, Qifeng (Public Library of Science, 2013)
β(2) adrenergic receptor (β(2)AR) regulated many key physiological processes by activation of a heterotrimeric GTP binding protein (Gs protein). This process could be modulated by different types of ligands. But the details about this modulation process were still not depicted. Here, we performed molecular dynamics (MD) simulations on the structures of β(2)AR-Gs protein in complex with different types of ligands. The simulation results demonstrated that the agonist BI-167107 could form hydrogen bonds with Ser203(5.42), Ser207(5.46) and Asn293(6.55) more than the inverse agonist ICI 118,551. The different binding modes of ligands further affected the conformation of β(2)AR. The energy landscape profiled the energy contour map of the stable and dissociated conformation of Gαs and Gβγ when different types of ligands bound to β(2)AR. It also showed the minimum energy pathway about the conformational change of Gαs and Gβγ along the reaction coordinates. By using interactive essential dynamics analysis, we found that Gαs and Gβγ domain of Gs protein had the tendency to separate when the inverse agonist ICI 118,551 bound to β(2)AR. The α5-helix had a relatively quick movement with respect to transmembrane segments of β(2)AR when the inverse agonist ICI 118,551 bound to β(2)AR. Besides, the analysis of the centroid distance of Gαs and Gβγ showed that the Gαs was separated from Gβγ during the MD simulations. Our results not only could provide details about the different types of ligands that induced conformational change of β(2)AR and Gs protein, but also supplied more information for different efficacies of drug design of β(2)AR.